Gêneros textuais acadêmicos e ensino da língua inglesa: um caminho para a motivação e a autonomia - RODRIGUES, Larissa Dantas (Universidade Federal do Pará, 2011)
In the academic environment, when asked to write academic genres, the undergraduate students in general have difficulties related to their content and textual organization. Therefore, these reading and writing practices are in general inhibitors of motivation and autonomy. From this perspective, I developed an action research with students of the sixth semester of the English Letters Course at UFPA aiming to verify in which way the application of a pedagogical proposition composed of the appropriation, production and publication of academic genres can develop those undergraduate students’ motivation and autonomy. This research is based on the theories of motivation (DÖRNYEI, 2001; USHIODA, 1996), autonomy (BENSON, 2001; SCHARLE & SZABÓ, 2000), and textual genres in the socio-rhetorical perspective (SWALES, 1990; BAZERMAN, 2006). The results presented try to offer possibilities of a systematic teaching that prepares the undergraduate Letters student to a more motivating and autonomous text production. Moreover, after experiencing a meaningful application of genres, it is expected that those future teachers will deal more effectively with other genres in their classrooms.